Clinical outcomes and recipient vessel selection for free flap transfer following arteriovenous malformation resection. Issue 1 (2nd January 2019) - Fujiki, Masahide; Ozaki, Mine; Iwashina, Yuki; Takushima, Akihiko
Abstract: Background: Arteriovenous malformation (AVM) is a rare vascular lesion that is difficult to treat. Radical surgical resection followed by free flap transfer is currently one of the preferred treatments, and this study aimed to assess the selection of recipient vessels and clinical outcomes for free flap transfer after AVM resection to establish better surgical management. Methods: Data from 22 consecutive patients who underwent free flap transfer after AVM resection were retrospectively reviewed. Of these, AVMs were located at the head and neck of 11 patients and at the extremities of another 11 patients. The first choice for a recipient vessel was a normal artery or vein. However, in the absence of suitable alternatives, the feeding arteries or drainage veins were employed as recipient vessels. Patient backgrounds and postoperative outcomes were evaluated. Results: Two patients required double flap transfer to cover the defects. Hence, a total of 24 flaps were transferred. A normal artery could be used in all cases of head and neck lesions, whereas a feeding artery was used in all cases of extremity lesions. On the other hand, a normal vein could be used in all cases as the recipient vein. No anastomotic failure or flap loss occurred postoperatively. Conclusion: Free flap transfer is feasible and safe even after AVM resection. The feeding artery can be used as the recipient artery in the absence of a normal artery especially for AVMs in the extremity although the safety of the drainage vein as the recipient vein remains unclear. Abbreviations: AVM: arteriovenous malformation; MRI: magnetic resonance imaging; 3DCT: threedimensional computed tomography; HN: head and neck; NR: not reported